Antipyretic Activity Test of Rambutan (Nephelium lappaceum L.) Seed in White Male Mice (Mus musculus) - Fadilah, Nitya Nurul; Nofriyaldi, Ali; Junaedi, Suna Agustine (Recent Developments in Chemistry and Biochemistry Research Vol. 5, 2024)
The rambutan plant (Nephelium lappaceum L.) empirically contains flavonoids. Flavonoid has many kinds of bioactivity which function as antipyretic, analgesic, and anti-inflammatory effects and can help reduce fevers. There have not been many studies conducted on rambutan seeds as a pain and fever reliever. Fever is a sign that the body is fighting infection or bacteria in the body, usually, the body temperature has increased greater than normal body temperature (> 37.2oC). The purpose of this study was to prove the antipyretic activity of rambutan seed extract against white male mice induced by the DPT-HB-Hib vaccine. This study used an experimental method which was divided into 5 treatment groups, namely, negative control of 1% Na CMC, positive control of paracetamol 1.3 mg/20 g BW of mice, and three groups of rambutan seed extract doses of 37.5 mg, 75 mg, and 150 mg/20 g BW mice. Fresh rambutan fruit was taken from Cikalang Tengah village, Tawang sub-district, Tasikmalaya City. Temperature measurements were carried out for 180 minutes with 30-minute intervals. The data obtained were analyzed by ANOVA test and LSD test. ANOVA test results for 180 minutes obtained p-value = 0.035, which means that there is a significant difference in temperature reduction in the five treatment groups, while the LSD test results for 180 minutes, the most effective dose is dose II of 75 mg/20 g BW in mice compared to other doses and did not have a significant difference with the positive control (paracetamol) because it had a comparable effect in reducing fever temperature in mice (Mus musculus). The dose III for 150mg/BW has an effectiveness rate of 98.11%. The highest antipyretic effectiveness falls to dose II for 75 mg/20g BW (98.58%), and the results are statistically significant.